The Interaction Between Typically Developing Students and Peers With Autism Spectrum Disorder in Regular Schools in Ghana: An Exploration Using the Theory of Planned Behaviour - Opoku, Maxwell Peprah; Nketsia, William; J-F,; Mprah, Wisdom Kwadwo; Agyei-Okyere, Elvis; Safi, Mohammed (Frontiers in Psychology, 2021)
The purpose of this study is to assess the intention of typically developing peers towards learning in the classroom with students with Autism Spectrum Disorder (ASD). In developing countries, such as Ghana, the body of literature on the relationship between students with disabilities and typically developing peers has been sparsely studied. Using Ajzen’s theory of planned behaviour as a theoretical framework for this study, 516 typically developing students completed four scales representing belief constructs, attitudes, subjective norms and perceived behavioural controls (self-efficacy), hypothesised to predict behavioural intention. The data were subjected to a t-test, analysis of variance and structural equation modelling. The modelling confirmed the combining ability of attitude, subjective norms and perceived behavioural controls to predict intention. We conclude by revealing the need for policymakers to consider designing programmes aimed towards promoting social relationships between students with ASD and typically developing peers.